O trabalhador rural e a propriedade da terra: o surgimento do Sindicato dos Trabalhadores Rurais de Passo Fundo (1962-1970) - Moretto, Milena (2020)
This research seeks to understand the advent of rural unionism in the northern region of the state of Rio Grande do Sul, more precisely the Rural Workers Union of Passo Fundo (1962-1970); seeking to identify and characterize the first associates and their properties. For the analysis, the membership forms for the Rural Workers Union of Passo Fundo from 1962 to 1970 are used as sources, which in essence present the member, his possession and his production. The time frame is the first years of STR in Passo Fundo, which began its activities in 1962 in the region and the years of consolidation of the union in the municipality.